Pengaruh kandungan informasi laporan laba rugi terhadap reaksi pasar modal Indonesia (Studi Kasus Pada Perusahaan Yang Listing Di BEI Periode 2011) - Faridh, Dika Miftah; Nurmayanti, Poppy; Kurnia, Pipin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine empirically the influence of the information content of the income statement to the stock market reaction . In this research data collection companies that serve as the sample is based on the following criteria : 1 ) All the companies listed on the Stock Exchange for 2011 except banks and financial institutions . 2 ) Has the financial statements ended December 31, 2011 . 3 ) The financial statements are presented in the currency. 4 ) Having a complete set of financial statements and can be obtained . 5 ) Data taken an accounting profit , not accounting the consolidated income statement . 6 ) Have a complete data regarding date of publication of financial reports and stock prices . Based on these criteria the company obtained 59 samples .Results of this study indicate that the statement of income has a significant effect on the stock market reaction . This suggests that the income statement can be use to predict how the stock market reaction .Keywords : income statement , capital market reactions